2012
DOI: 10.1038/ejhg.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Brugada-like and short QT electrocardiogram linked to SCN5A mutation

Abstract: Mutations in the a-subunit of cardiac sodium channel gene SCN5A can lead to the overlapping phenotypes of both the Brugada and type 3 long QT syndromes. However, the combination of Brugada and a short QT phenotype resulting from mutation in SCN5A has not previously been described. A man with concomitant Brugada-like and short QT electrocardiogram (ECG) was identified and the SCN5A gene was sequenced. Whole-cell patch clamp analysis of human embryo kidney (HEK) 293 cells expressing a SCN5A channel with the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 18 publications
0
16
2
Order By: Relevance
“…It is however obvious that these findings cannot explain the very severe phenotype observed in this family. In addition, these results are difficult to reconcile with the ones from a recent study where no functional expression of this p.R689H variant was observed. We can only speculate on the fact that experimental details such as the plasmids or cells used may be at the origin of this discrepancy.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…It is however obvious that these findings cannot explain the very severe phenotype observed in this family. In addition, these results are difficult to reconcile with the ones from a recent study where no functional expression of this p.R689H variant was observed. We can only speculate on the fact that experimental details such as the plasmids or cells used may be at the origin of this discrepancy.…”
Section: Discussioncontrasting
confidence: 91%
“…When analyzed with the “sorting tolerant from intolerant” (SIFT) algorithm, p.R689H was classified as “damaging,” while the Polyphen software classified it as “benign”; p.R689C was classified as “damaging” by SFIT and “possibly damaging” using Polyphen . These 2 variants were already reported several times in the literature (summarized in Table ), either in patients with LQTS or BrS, or in individuals from control cohorts.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Crotti et al [128] identified six patients (4.6%) with a mutation in one of the 12 other genes tested: two with a mutation in CACNB2b and one with a mutation in each of HCN4 , KCND3 , KCNJ8, and SCN1Bb . The low <2% yield of mutations involving the L-type calcium channel genes CACNA1C , CACNB2b, and CACNA2D1 is in contrast with previous findings of 8.5% for CACNA1C and CACNB2b only [131] and 12.3% for CACNA1C , CACNB2b, and CACNA2D1 all three [132] and may be related to the presence of a concomitant short QT interval [128], as in the study by Burashnikov et al [132] and also reported by Hong et al [133]. …”
Section: Primary Electrical Cardiac Diseasescontrasting
confidence: 78%